2016
DOI: 10.1186/s12891-016-1188-3
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic discoid lateral meniscus: a clinical and arthroscopic study in a Chinese population

Abstract: BackgroundDiscoid lateral meniscus (DLM) is relatively common in East Asia..Symptomatic discoid lateral meniscus (SDLM) is an important indication for knee arthroscopic surgery. However, studies investigating SDLM are rare. The purpose of this study was to evaluate the clinical characteristics and intra-articular variants of SDLM in a Chinese population.MethodsWe retrospectively reviewed all patients with SDLM from January 2005 to December 2014 in our hospital. Clinical variables included gender, age, duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Chen et al . 20 have reported the symptoms of discoid meniscus injury in both men and women. Popping and snapping were mainly found in males, and restricted ROM was mainly found in females.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al . 20 have reported the symptoms of discoid meniscus injury in both men and women. Popping and snapping were mainly found in males, and restricted ROM was mainly found in females.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic discoid lateral meniscus tear occurs mainly in young and middle-aged women in the Chinese population. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, discoid lateral meniscus (DLM) is common. The reported incidence of DLM is 13% in china [18], 16.6% in Japan [23], 10.9% in Korea [26] and 5.8% in India [39]. The prevalence of DLM in the western population ranges from 0.4% to 17% [48].…”
Section: Introductionmentioning
confidence: 99%
“…Although the overall postoperative clinical outcomes of symptomatic DLM are acceptable [11,17,38], the outcomes still differ among individuals, possibly as a result of the diversity in patient characteristics and treatments [31]. Recently studies have reported several factors that in uence postoperative effect in symptomatic DLM, but the sample sizes used in these studies are uneven, and the results are inconsistent [10][11]19,28]. The present research independently analyses 14 possible in uences, including gender, body mass index (BMI), and other factors, in a larger series of patients with the goal of identifying the factors that in uence postoperative outcome in patients with symptomatic DLM and thereby guiding clinical application.…”
Section: Introductionmentioning
confidence: 99%